Improving Graphical and Numerical Representational Competence Coherence with Laboratory Investigation and Computer to Solve Problem-Solving of Geometry Optical Materials - Wawan Bunawan; Satria Mihardi; Pardomuan Sitompul; Irham Ramadhani (Jurnal Penelitian Pendidikan IPA, 2023)
Learning physics through the investigation of phenomena using practicum equipment in the laboratory is the real core of learning physics. The basic competence of prospective science teachers towards understanding concepts through investigating phenomena is well developed. The achievement of other, more abstract concept representation competencies such as numerical, graphical, and mathematical representations requires new methods or ways in the learning process. The development of computer technology as part of further investigation of learning in the laboratory needs to be developed to facilitate learning. The purpose of this research is to investigate how to improve competence in understanding concepts based on verbal representations (Verb Rep) in the form of investigations of phenomena, to achieve multiple representations (MR) (Formal Representation, Numerical Representation, Graphical Representation, Pictorial Representation) with computer-based learning. The results showed that the conventional group (N=30; M=72.87; SD = 7.03; SE = 1.28) had a lower average score on the test results than the experimental group (N = 30; M = 83.27; SD = 4.93; SE = 0.89). Independent mean statistical tests showed significant differences (t (30) = -6.63; p <0.001; r = 0.78) between groups learning to use one representation (conventional) and those using MR to solve problem-solving cases of lens content and curved mirrors, with the category of effect size (r)0.78 exceeding 0.50 (large effect).